Pemanfaatan Media Sosial Untuk Mendorong Kesadaran Lingkungan - Putri, Riski Dwi; Amelia, Dita; Shabira, Syahla Malika (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the use of social media in promoting environmental awareness among the public, considering the increasing awareness of the negative impacts of climate change and environmental pollution. This study has three main objectives: first, to identify the most effective types of content in increasing public awareness and participation in environmental issues; second, to evaluate the impact of environmental campaigns on social media platforms on changes in public behavior and attitudes; and third, to examine the role of collaboration with influencers and environmental organizations in expanding the reach of environmental awareness messages. By using quantitative survey methods and qualitative elements, it is hoped that the results of this study can provide valuable insights for the development of more effective communication strategies in increasing awareness and collective action on environmental issues in Indonesia.